PERSEPSI SISWA TERHADAP LAYANAN LABORATORIUM KOMPUTER PADA MATA PELAJARAN KOMPUTER AKUNTANSI DI SMKN 3 PONTIANAK - Aryo Dindamarsa; Bambang Genjik Sumartono; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractStudents' perceptions of accounting computer laboratory services are the activities of students in conducting an assessment of accounting computer laboratory services in schools. The role of the laboratory is very essential in terms of laboratory of accounting servicesin which, the duties of the laboratory assistant are such as controlling the students who use the computer, guiding, and maintaining the laboratory. This research aims to know students' perceptions towards the service of the laboratory of accounting in SMK Negeri 3 Pontianak. The researcher used qualitative with descriptive approach as the methodology. The sample of thisresearchwere 8 (eight)students of SMKNegeri 3 Pontianak. Technique of data collection is interview. The results showed that students' perceptions towards the service of laboratory of accounting was already good but it still needs some improvements according to the students. Keywords: Accounting, labotary Services, Students Perception